Peran Pendidikan Akhlak dalam Mengatasi Kenakalan Remaja di Lingkungan MA AL-Kreatif al-Mubaraak Bengkulu - Intan Puspa Sari; Fatma Wardah; Cici Amelia Putri; Yuni Faddila S; Adisel Adisel (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
AbstractJuvenile delinquency is a form of deviant behavior often found during adolescence, a period marked by identity searching, emotional instability, and strong environmental influence. Moral education plays a crucial role as a guiding force to help adolescents avoid negative behavior such as fighting, truancy, smoking, and minor crimes. As an educational institution, madrasahs have a vital role in fostering students’ character. MA AL-Kreatif al-Mubaraak Bengkulu implements moral education intensively through formal lessons, religious activities, and daily positive habits. This study aims to analyze the role of moral education in reducing juvenile delinquency at the school. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings show that moral education, implemented through teacher role modeling, religious routines, and character-building activities, significantly contributes to shaping students’ positive behavior. It helps create a disciplined, religious school environment and proves that moral education has a practical impact on improving adolescent behavior.Keywords: Moral Education, Juvenile Delinquency, Madrasah